Flashcard-Assisted Teams Games Tournament (TGT) Model on Students' Reading Ability in Grade 1 SDN 211 Pinrang - Fatmawati Fatmawati; Baharuddin Baharuddin; Asbar Asbar (Universitas Muhammadiyah Enrekang, 2024)
This study aimed to describe the implementation of the Teams Games Tournament learning model assisted by flashcards and analyze its effectiveness on the reading ability of first-grade students at Sekolah Dasar Negeri 211 Pinrang. The research employed a quantitative approach with a quasi-experimental nonequivalent control group design, involving 56 first-grade students divided into experimental and control groups, each with 28 students. The experimental group received instruction using the Teams Games Tournament model with flashcards over 10 meetings, while the control group followed conventional learning. Data on reading ability were collected through oral and written tests, as well as observations of teacher and student activities. Data analysis used descriptive statistics to depict reading ability and inferential statistics through a t-test to test hypotheses. The results showed that the Teams Games Tournament model with flashcards was implemented very well, with an average teacher activity implementation rate of 91.8% and student activity at 87.7%. The experimental group’s reading ability significantly improved from an average of 55.68 on the pretest to 78.36 on the posttest, compared to the control group’s increase from 56.25 to 65.32. The t-test yielded a t-value of 5.235, greater than the t-table value of 2.004, with a significance of 0.000, indicating the model’s effectiveness in enhancing students’ reading ability. The reading whole words indicator showed the most significant improvement at 50%